Rotordynamics of Two‐Pole Turbo Generators with Refined Modelling of the Unbalanced Magnetic Pull. Issue 1 (21st October 2015) - Boy, Felix; Hetzler, Hartmut
Abstract Within this contribution the rotordynamic behaviour of two‐pole turbo generators is discussed. In the investigation a basic model originally proposed by Kellenberger [1], introducing a refined description of the unbalanced magnetic pull (UMP), is reviewed and extended. The analysis comprises the investigation of lateral stability behaviour and stationary torque characteristic for a magnetic eccentricity. There are two main results of the contribution: firstly it is shown, that the non‐radial component of the UMP has the same structure as the restoring forces due to a non‐circular shaft, but opposite sign. Secondly it can be seen from the extended model, that an eccentric point of application of the UMP may change the systems stationary torque characteristic significantly. (© 2015 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)